2016
DOI: 10.4191/kcers.2016.53.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Proton Conduction in Nonstoichiometric ∑3 BaZrO3 (210)[001] Tilt Grain Boundary Using Density Functional Theory

Abstract: We investigate proton conduction in a nonstoichiometric ∑3 BaZrO 3 (210)[001] tilt grain boundary using density functional theory (DFT). We employ the space charge layer (SCL) and structural disorder (SD) models with the introduction of protons and oxygen vacancies into the system. The segregation energies of proton and oxygen vacancy are determined as -0.70 and -0.54 eV, respectively. Based on this data, we obtain a Schottky barrier height of 0.52 V and defect concentrations at 600K, in agreement with the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This study strengthens previously suggested mechanisms of improving proton transport by decreasing dopant-lattice interaction [173,215]. For speci c insight on the tilt grain boundary effect, Kim et al [216], utilize space charge layer and structural disorder to incorporate proton and oxygen vacancies into the system. Based on segregation energies, the energy barriers for proton transport are calculated.…”
Section: Theoretical Studies On Bzo Proton Conductorsupporting
confidence: 83%
“…This study strengthens previously suggested mechanisms of improving proton transport by decreasing dopant-lattice interaction [173,215]. For speci c insight on the tilt grain boundary effect, Kim et al [216], utilize space charge layer and structural disorder to incorporate proton and oxygen vacancies into the system. Based on segregation energies, the energy barriers for proton transport are calculated.…”
Section: Theoretical Studies On Bzo Proton Conductorsupporting
confidence: 83%
“…These regions form because of segregation of positively charged defects (protons and oxygen vacancies) to the GB cores and become depleted of protons, which reduces the conductivity across the GB. Many experimental and theoretical studies of BZO have been conducted where space-charge potentials between 0.3 and 0.9 V have been found depending on doping and sintering conditions. While the space-charge model also has been used to explain GB effects in BCO, fewer in-depth studies of this phenomenon exist for this material.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been investigated intensively and it is generally accepted that the high GB resistance is due to positively charged GB cores, resulting in space-charge regions surrounding the cores which are effectively depleted of protonic charge carriers. [9][10][11] Theoretical studies of a variety of different GBs, [12][13][14][15][16][17][18][19][20] and also a recent experiment using atom-probe tomography, 21 have shown that the charged GBs stem from accumulation of both doubly charged oxygen vacancies ðv O Þ and protons ðOH O Þ. None of these theoretical studies, however, consider free energies of defect segregation, but rather the energy at zero Kelvin thus neglecting the temperature dependence and zero-point vibrational contribution to defect segregation energies.…”
Section: Introductionmentioning
confidence: 99%